Expansion of gut associated immunoglobulin A secreting lymphocytes in rheumatoid arthritis correlates with high levels of serum IgA (1993)
We report the emergence of polyclonal expansion of gut lymphocyte associated tissues producing IgA in a patient with rheumatoid arthritis associated with a high serum IgA concentration. The role of IgA in rheumatoid arthritis is reviewed.